A Co-optimization Model of Natural Gas Supply and Electric Power Systems - Worawat Nakawiro (My University, 2019)
In Thailand, natural gas has been the primary source of fuel for power generation for the past few decades due to availability of indigenous resources.With continuous load growth and near depletion of domestic natural gas supply, renewable energy will play an increasing role in power industry in a close future.To achieve that, energy storage would become the key enabler.Therefore, this paper proposes a co-optimization steady-state model of a -coupled system of gas supply network and electric power system with integration of an energy storage device namely power-to-gas.The IEEE-14 bus power system coupled with the 20-node and 24 pipeline natural gas system is used to verify effectiveness of the proposed method through computer simulation.The results show the capability in maintaining the system variables within the statutory security limits and reducing power losses.Moreover, the proposed method has another feature that can optimally curtail loads of the two systems when experiencing stressful conditions.
Keywords: Power-to-Gas; Energy supply; Integrated Energy Systems Optimization